2015
DOI: 10.1158/1940-6207.capr-14-0372
|View full text |Cite
|
Sign up to set email alerts
|

Sarsaparilla (Smilax Glabra Rhizome) Extract Inhibits Cancer Cell Growth by S Phase Arrest, Apoptosis, and Autophagy via Redox-Dependent ERK1/2 Pathway

Abstract: Cancer is still the major cause of death across the world. Regular approaches cannot effectively solve the emerging problems, including drug/radiation resistance, side effects, and therapeutic ineffectiveness. Natural dietary supplements have shown effectiveness in the prevention and treatment of cancer. Sarsaparilla (Smilax Glabra Rhizome) has growth-inhibitory effects on several cancer cell lines in vitro and in vivo, with little toxicity on normal cells. However, the mechanism underlying its function remain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…As one of the most popular traditional Chinese medicines, it is used for relieving dampness, detoxifying, and easing joint movement [ 1 , 2 ]. Pharmacological studies indicate that it has anti-inflammatory, anti-tumor, and immunomodulatory activities and protective effects against hepatocyte damage [ 3 , 4 , 5 ]. Polyphenols are bioactive ingredients that have not only anti-inflammatory activities but also higher content expression in the rhizome of S. glabra .…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most popular traditional Chinese medicines, it is used for relieving dampness, detoxifying, and easing joint movement [ 1 , 2 ]. Pharmacological studies indicate that it has anti-inflammatory, anti-tumor, and immunomodulatory activities and protective effects against hepatocyte damage [ 3 , 4 , 5 ]. Polyphenols are bioactive ingredients that have not only anti-inflammatory activities but also higher content expression in the rhizome of S. glabra .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, to the best of our knowledge, the present study demonstrated for the first time the potential benefits of co-administration of MTX with SGR. Co-administration of SGR may be beneficial for therapy of lung cancer and splenic carcinoma, osteosarcoma, and liver diseases, but may reduce the therapeutic effect of treating cancer in the digestive tract, systemic lupus erythematosus and psoriasis (50)(51)(52)(53)(54). The herb-drug interaction may be associated with the activity change of transporters.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of apoptosis of cancer cells was suggested. This study provided a theoretical basis for sarsaparilla as an anticancer agent [38] .…”
Section: Laboratory Studies On Cancer Cell Linesmentioning
confidence: 93%